Modulation of cerebral catecholamine concentrations during hyperphenylalaninaemia. - Brass, C A (1982)
Hyperphenylalaninaemia induced by daily injections of alpha-methylphenylalanine plus phenylalanine caused 20-40% decreases in cerebral dopamine (3,4-dihydroxyphenethylamine) and noradrenaline in 7- and 11-day-old rats. alpha-Methylphenylalanine alone as well as phenylalanine alone caused cerebral dopamine depletion. However, the effects were not additive, in that the depletion caused by alpha-methylphenylalanine was greater, not less, than that after treatment with both it and phenylalanine. Increased concentrations of tyrosine in the brain, owing to administered or endogenously formed tyrosine, could overcome the effect of excess phenylalanine on cerebral dopamine content. The fact that the inhibition of tyrosine hydroxylase by phenylalanine (or alpha-methylphenylalanine) in vitro was overcome by tyrosine concentrations similar to those effective in vivo further implicates the tyrosine hydroxylase inhibition as the mechanism underlying the dopamine depletion in hyperphenylalaninaemia. These results provide a theoretical basis for elevation, by tyrosine supplementation, of the cerebral phenylalanine/tyrosine ratio as a possible treatment modality for phenylketonuria.